Dual combining transition metal hybrid nanoparticles for ammonia borane hydrolytic dehydrogenation - Filiz, Bilge Coskuner; Figen, Aysel Kanturk; Piskin, Sabriye (ELSEVIER SCIENCE BV, 2018)
A new hybrid of nanoparticles designed to enable efficient catalysis for hydrogen generation (NPs) include a dual combination of Co, Ni, and Cu transition metals. These nanoparticles are made by altering metals and molar ratios (x: 0.25, 0.50, and 0.75) and synthesized for hydrogen generation by hydrolytic dehydrogenation of ammonia borane (NH3BH3). A synergistic effect of dual combination on the induction period and dehydrogenation rate (DR) is found. Kinetic interpretation and thermodynamic studies demonstrate that the Co0.50Cu0.50/NPs catalyst shows superior activation (DR = 10.561 H-2 min(-1).g(-1)cat and E-a = 38.12 kJ mol(-1)) with a synergistic effect and meet the criteria of The United States Department of Energy (DOE) targets for onboard hydrogen production systems for light-duty vehicles.
Keywords: Dual combining; Hybrid nanoparticles; Ammonia borane; Dehydrogenation; Kinetic; Thermodynamic; HIGHLY EFFICIENT DEHYDROGENATION; HYDROGEN GENERATION; CATALYTIC HYDROLYSIS; ALLOY NANOPARTICLES; CO-B; SYNERGETIC CATALYSIS; SODIUM-BOROHYDRIDE; NI; EVOLUTION; CARBON; Chemistry; Environmental Sciences & Ecology